Exploring hedonic purchase behaviors : essays on impulse buying behaviour - Piyush, Sharma (2008)
A central question in consumer research is how consumers make purchase decisions. Prior research has highlighted a need to explore the relationships between scales representing different forms of purchase behavior to yield insights into the structure of purchase-related personality traits and help understand how these traits are organized within an individual consumer. This need is addressed in three different but inter-related essays, all in the context of hedonic purchase behaviors. These essays explore relevant consumer traits and their association with purchase behavior in different contexts to provide a better understanding of the complex motivation and psychological processes underlying these behaviors. In the first essay, the association of two common hedonic purchase behaviors (impulse buying and variety seeking) with three relevant consumer traits (consumer impulsiveness, optimum stimulation level and self-monitoring) is explored using two empirical studies. In the second essay, the issue of cross-cultural measurement equivalence of consumer impulsiveness scales is investigated using confirmatory factor analysis and structural equation modeling approaches with a series of studies in Singapore and the US. Finally, in the third essay incidence of impulse buying in explored in the services context and some key differences and similarities are highlighted with that in the products context.